MODELING SPEECH THERAPY ACTIVITY IN SPEECH CORRECTION OF CHILDREN WITH PSEUDOBULBAR DYSARTHRIA - Toshturdiyeva Zoyira Dusmurod kizi (Western European Studies, 2024)
This article discusses the modeling of speech therapy activities in correcting the speech of children with pseudobulbar dysarthria. The strategic and tactical tasks of correctional work are described, the stages and directions of organizing speech therapy work for the correction of speech disorders with pseudobulbar dysarthria in preschool children are considered. In modern society, speech pathologies in preschool children are often found. A more common form of dysarthria in preschool children is pseudobulbar dysarthria, which makes it urgent to study the psychological and pedagogical features of the development of preschool Children with pseudobulbar dysarthria and the work of a speech therapist.
Keywords: speech therapy; pseudobulbar dysarthria; speech correction